Meta-analysis of quality of life in children and adolescents with ADHD: By both parent proxy-report and child self-report using PedsQL™. (April 2016) - Lee, Yi-chen; Yang, Hao-Jan; Chen, Vincent Chin-hung; Lee, Wan-Ting; Teng, Ming-Jen; Lin, Chung-Hui; Gossop, Michael
Highlights: This meta-analysis supports the negative impact of ADHD on HRQOL in children and adolescents. A moderate effect of child's ADHD in physical HRQOL and a severe effect in psychosocial HRQOL are noted. These effects are consistent between parent proxy-reports and child or adolescent self-reports. Age is negatively related to HRQOL in children and adolescents with ADHD. A moderate association is noted between age and parental ratings of child's emotional HRQOL. Abstract: Attention deficit hyperactivity disorder (ADHD) is a prevalent developmental disorder that seriously and negatively impacts a child's health-related quality of life (HRQOL). However, no meta-analysis has been conducted to examine the magnitude of impact, domains affected and factors moderating the impact. This review included nine studies that compared HRQOL of children or adolescents with ADHD with those with typical development using both child self-reports and parent proxy-reports. Seven among nine studies were meta-analytically synthesized to examine the degree of impact of ADHD on children and adolescents, parent–child discrepancy, and the moderators. The results indicate that ADHD impact a child's or adolescent's HRQOL negatively with a moderate effect in physical and a severe effect in psychosocial (i.e., emotional, social, and school) domains. Parental ratings of overall HRQOL in children or adolescents with ADHD were not significantly different from child's ratings when compared with typically developing children and adolescents. Age was negatively associated with all domains of HRQOL in children and adolescents with ADHD both by parent- and child-ratings, and the strongest effect was found in parental ratings of child's emotional HRQOL, with a moderate correlation. This meta-analysis suggests that HRQOL may be assessed in children and adolescents with ADHD both by parent proxy- and child self-reports, and that interventions may be planned accordingly. Future meta-analysis may explore how measures of HRQOL and other factors including child, parental, familiar and school characteristics influence the impact of ADHD and the parent–child agreement in children and adolescents.